Insights from a Catholic school’s transition to distance learning during Covid-19 - Wright, Samuel; Park, Yun Soo; Saade, Ahmed J. (Taylor and Francis, 2024)
Drawing upon 15 semi-structured interviews with teachers at a Catholic school in the British city of Hull, we offer new qualitative insights on the effects of students’ unequal access to digital tools when switching to distance learning in the context of COVID-19 school closures. During the 2020–2021 academic year, this school serving pupils from highly dissimilar socioeconomic backgrounds distributed 300 laptops to students who did not own any digital learning device. It emerges that students with limited access to devices suffered negative impacts on their academic performance, and that this effect also applied to students who had access to a mobile device and hence did not receive a laptop. Our interviews also suggest that having to share a device with another family member leads to more absenteeism and a fall in academic attainment. Low parental involvement is shown to have negative effects on students’ attainment, particularly for children from deprived backgrounds. Finally, poorer students are seen to become isolated from peers, with diminishing social skills throughout lockdowns due to their lack of access to digital tools.
Keywords: COVID-19; digital learning; distance learning; educational inequality; school closure